Socio-economic impact of CSR activities of an Islamic Banking: A Case of Islami Bank Bangladesh Limited - Shahnewaz, Syeda Tanjila (Asian Business Review, 2016)
This paper examines the practices and driving philosophy of corporate social responsibility (CSR) by Islami Bank in Bangladesh and to evaluate the need to modify CSR program of the organization to enhance its effectiveness. The purpose of the paper is to study the underlying drivers of the CSR program undertaken by the Islami Bank Bangladesh Limited and to explore if the CSR activities are planned as a holistic approach to social development. This study covers a period of 5 years ranging from 2010 – 2014 using secondary data from annual reports of the bank, relevant articles, websites, Bangladesh Bank publications, newspaper, journal and magazines. This study found that the Islami Bank Bangladesh had linked its CSR program as core business strategy to grow business with shared prosperity with its surrounding community. However, it has the improvement opportunity to create a synergy by bundling all its CSR activities as a holistic program. If appropriately planned, such program will promote self-sufficiency, create new jobs and enable economic development under alternative livelihood program as suitable in the locality. JEL Classifications: M 14